Characteristics of multiple basal cell carcinomas: The first study on Japanese patients. Issue 10 (23rd July 2018) - Adachi, Koji; Yoshida, Yuichi; Noma, Hisashi; Goto, Hiroyuki; Yamamoto, Osamu
Abstract: Basal cell carcinoma (BCC), the most frequent skin cancer, has been increasing in incidence. However, the characteristics of multiple BCC have not been clarified in Japan. Therefore, we conducted a retrospective study to elucidate the features of multiple BCC compared with solitary BCC. The study population consisted of 327 patients with histopathologically proven BCC who were referred to the Department of Dermatology in Tottori University Hospital between November 2006 and April 2016. Of the 327 patients, 304 (93.0%) had solitary BCC and 23 (7.0%) had multiple BCC. The mean age of the patients with solitary BCC was 74.7 years (range, 31–102) and that of patients with multiple BCC was 79.3 years (range, 63–91). There was a significant difference in mean age between the two groups ( P = 0.01). Approximately four‐fifths of the BCC were located on the head or neck in the total study population. In the group of patients with multiple BCC, the incidence of lesions on the head and neck was lower and that on the trunk was higher than those in patients with solitary BCC. There was a significant difference in the tumor site between the two groups ( P < 0.0001). With respect to tumor histopathology, the ratio of superficial BCC was significantly higher in the group of patients with multiple BCC than in the group of patients with solitary BCC ( P < 0.0001). In conclusion, we demonstrated that older age, truncal location and superficial histopathological type of tumor are features of multiple BCC in Japanese subjects.